37th International Symposium on Microarchitecture (MICRO-37'04)
DOI: 10.1109/micro.2004.27
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Superblock Scheduling Using Enumeration

Abstract: The superblock is a scheduling region that is used by compilers for exploiting instruction-level

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…The basic block instruction scheduling problem is to find a minimum length schedule for a basic block-a straight-line sequence of code A.M. Malik · T. Russell · M. Chase · P. van Beek ( ) School of Computer Science, University of Waterloo, Waterloo, Canada e-mail: vanbeek@uwaterloo.ca with a single entry point and a single exit point-subject to precedence, latency, and resource constraints. 1 Basic block scheduling is important in its own right and also as a building block for scheduling larger groups of instructions such as superblocks (Cooper and Torczon 2004;Shobaki and Wilken 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The basic block instruction scheduling problem is to find a minimum length schedule for a basic block-a straight-line sequence of code A.M. Malik · T. Russell · M. Chase · P. van Beek ( ) School of Computer Science, University of Waterloo, Waterloo, Canada e-mail: vanbeek@uwaterloo.ca with a single entry point and a single exit point-subject to precedence, latency, and resource constraints. 1 Basic block scheduling is important in its own right and also as a building block for scheduling larger groups of instructions such as superblocks (Cooper and Torczon 2004;Shobaki and Wilken 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, instruction scheduling has been employed by compilers to exploit instruction level parallelism in straight-line code in the form of basic blocks [Heffernan and Wilken 2005; and superblocks [Heffernan et al 2006;Shobaki and Wilken 2004;. In this section we review the different approaches towards solving the spatial scheduling problem.…”
Section: Related Workmentioning
confidence: 99%
“…Clearly, the number of cycles depends on the quality of the scheduling algorithm, and most of all on the two-dimensional layout that provides communication channels for the qubits. To extract the physical communication resources for low-level networks such as level-1 error correction, we have employed the QPOS scheduling tool , which is based on traditional compiler scheduling heuristics [Chekuriet al 1996;Deitrich and Hwu 1996;Shobaki and Wilken 2004], and has demonstrated better circuit schedules than carefully hand-optimized layouts. In this manner, we can extrapolate that fully serialized error correction at level 2 will last approximately 0.3 seconds, which is two orders of magnitude longer than the time to error correct at level 1.…”
Section: Logical Qubit Design and Cost Of Error Correctionmentioning
confidence: 99%